Emotional perception and historical heritage: a segmentation of foreign tourists who visit the city of Lima - López-Guzmán, Tomás (2019)
ABSTRACT Purpose The purpose of this paper is to conduct an analysis of the relationships existing among three basic constructs in the visitor’s decision-making process (motivation and satisfaction) in a tourist destination that is a World Heritage Site, such as the city of Lima (Peru). Bearing in mind the perception of heritage by the foreign visitors, four types of tourists were determined: alternative tourists, cultural tourists, emotional tourists and heritage tourists. Design/methodology/approach This research uses the multivariate technique of grouping cases (K-means clusters) to analyse the similarity existing among the surveyed persons. From the groups or segments obtained, statistics and measurements of association were applied, which provide the information necessary to study the possible trends of association existing between variables from a table of bidimensional contingencies. In the same way, nonparametric statistical procedures were used (Kruskal–Wallis H test and the Mann–Whitney U test) with the aim of analysing significant differences among groups of the sample. Findings The results show the existence of four diverse motivational dimensions among the foreign tourists to visit Lima: hedonic, cultural, convenience and circumstantial. Of the four dimensions, the cultural aspect is the most relevant. The results show the existence of a specific Ibero-American heritage and cultural identity. Originality/value This paper contributes to the academic literature on the links of the tourist with the historical and monumental heritage location(s) visited by the tourist and the tourist’s behaviour while visiting the site. In fact, it is one of the first investigations carried out on this subject in Latin America.